Revision of Diplosynapsis Enderlein, 1914 (Diptera, Asilidae, Asilinae) with description of four new species - Vieira, Rodrigo; Rafael, José Albertino (Zootaxa, 2016)
The robber fly genus Diplosynapsis Enderlein, 1914 is reviewed and four new species are described—D. chela sp. nov. (Amazonas state, Brazil), D. fisheri sp. nov. (Guapiles, Heredia, Limon, Puntarenas province, Costa Rica), D. spina sp. nov. (Rio de Janeiro state, Brazil) and D. uncinata sp. nov. (Amazonas state, Brazil). A lectotype is designated for D. cellata (Schiner, 1868) pres. desig. and comments are made on D. remus Tomasovic, 2002. An identification key and illustrations are presented for all species.